The Influence of Academic Self-Efficacy and Peer Support on Students’ Learning Motivation in Mathematics - Isnawati, Alamanda Wahyu; Naqiyah, Najlatun; Khusumadewi, Ari; Nuryono, Wiryo (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study is to examine the influence of academic self-efficacy and peer support on students’ learning motivation in mathematics among junior high school students. It aims to identify whether academic self-efficacy and peer relationships contribute to increasing learning motivation in mathematics both partially and simultaneously. Methodology: This study using a quantitative approach with an ex post facto design involving 345 junior high school students selected through simple random sampling. Data were collected using standardized academic self-efficacy, peer support, and learning motivation scales. The data were analyzed using simple linear regression and multiple linear regression through SPSS version 27 to determine the magnitude and significance of the relationships. Main Findings: The findings revealed that academic self-efficacy and peer support both have significant positive effects on students’ learning motivation in mathematics. Academic self-efficacy emerged as the strongest predictor, while peer support acted as an important factor enhancing students’ learning motivation in mathematics. Simultaneously, both variables explained a substantial portion of the variance in mathematics learning motivation. Novelty/Originality of this study: This study shows that motivation to learn mathematics can be influenced by academic self-efficacy and peer support. It is important for teachers to involve peers in the learning process and providing valuable insights for guidance and counseling teachers to foster supportive and confidence-building learning conditions.